1999
DOI: 10.1021/jo9907437
|View full text |Cite
|
Sign up to set email alerts
|

Selective Anion Complexation by a Calix[4]pyrrole Investigated by Monte Carlo Simulations

Abstract: The complexation of anions by octamethylcalix [4]pyrrole 1 and 2,5-dimethylpyrrole has been investigated by energy minimizations in the gas phase and by Monte Carlo (MC) simulations in dichloromethane using the OPLS force field. In agreement with experiment, the 1,3-alternate conformation of 1, in which adjacent pyrrole rings are pointing in opposite directions, was shown to be the most stable conformation in the absence of a halide anion. The cone conformer of 1, having all pyrrole units in a parallel orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 27 publications
1
27
0
1
Order By: Relevance
“…Compared to the wealth of experimental studies of calix[4]arenes, their computational study lagged behind due to the large system size of calixaromatics that limited the methods that could be used in their study. Since 1990, computational studies have focused on structural features34–36 and properties37, 38 initially using molecular mechanics and later semi‐empirical methods such as PM3 and AM1 39–45. However, most of these studies were not able to accurately describe the structures and the conformational equilibria and therefore only yielded a very qualitative understanding of the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the wealth of experimental studies of calix[4]arenes, their computational study lagged behind due to the large system size of calixaromatics that limited the methods that could be used in their study. Since 1990, computational studies have focused on structural features34–36 and properties37, 38 initially using molecular mechanics and later semi‐empirical methods such as PM3 and AM1 39–45. However, most of these studies were not able to accurately describe the structures and the conformational equilibria and therefore only yielded a very qualitative understanding of the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, detailed analyses of the 1 H NMR spectra of compounds 1 a, 2 a, 3 , and 7 carried out in CD 2 Cl 2 , revealed that these prototypic species, while best described as being in conformations analogous to those seen in the solid sate, are nonetheless subject to dynamic distortions. As in the case of calix[4]pyrrole,43–45 these motions are rapid at room temperature and begin to slow on the NMR timescale only at 188 K. While detailed analyses of the conformations present at room temperature are ongoing, they are believed to involve principally breathing motions such as those illustrated in Scheme , although rapid interconversions between the dominant 1,3‐alternate and flattened partial‐cone conformations highlighted in these schemes (and seen in the solid state) and more minor species (e.g., cone) cannot be rigorously ruled out.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…DFT can also be used in the investigation of hydrogen-bonding interactions, provided that the accuracy limitations are understood. 36 Although some theoretical studies have been performed on the hydrogen-bonding interaction of halide anions with water, [37][38][39][40][41] cyclopeptide 42,43 and aromatic systems, [44][45][46][47][48][49] theoretical quantum-chemical calculations concerning oligourea macrocycles and their anion binding behavior are almost absent in the literature except for some scattered computational studies. 27,29,30 We present here results of DFT studies on a series of halide anions (F À , Cl À , Br À , and I À ) and nitrate ion bound to the oligourea 1 by multiple hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%